Race as a Historical Category in the 15th Century? Gender Coloniality and the Unfaithful Canarian Women (2024)
The theoretical framework of the studies stemming from the decolonial epistemological shift is grounded in the concept of coloniality. The feminist critique, specifically with the proposal of María Lugones, revised this theory by introducing the concept of gender coloniality, emphasizing the crucial importance of this oppression within the colonial system. This theory asserts the existence of, starting from 1495, a modern colonial world system of gender, built upon the centrality of the category of race in explaining the epistemological, economic, and cultural domination of the Western world over colonized territories. From a post-structuralist standpoint, we propose a historical analysisof the chronicles of the conquest of the Canary Islands, where we question the use of the category of race in the 15th century as the basis for differentiation, replacing it with others based on European colonial religious centrism, equally intersected by gender differences.